Primary Poverty: Evolving definitions, scope and implications (2017)
What is the face of poverty? How should a phenomenon so dynamic and fluid be ever captured by data? Seebohm Rowntree’s introduc tion of primary poverty as depiction of the poorest of the poor inthe 19th century provided the impetus that simplified the complicated nature of poverty and, likewise, raised questions about the generalizability of its context. Criticisms as to the nature and method of Rowntree has dominated poverty literature; yet, many of social scientists also assert the groundbreaking contributions of Rowntree’s work as pivotal to government policy and poverty-oriented institutions. Upon the release of Rowntree’s data about primary poverty of the working-class in York, there have been several attempts as to how to modify, enrich and even discredit the findings of Rowntree an all these efforts pave the way for the gradual transformation of several poverty measures that have provided so much data to governments in the world today.